2020
DOI: 10.1177/1076029620910793
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Risk Score for Prediction of Venous Thromboembolism in Patients With Lung Cancer

Abstract: This study aimed to develop and validate a risk score for early prediction of venous thromboembolism (VTE) in patients with lung cancer. A total of 827 patients with lung cancer from February 2013 to February 2018 in our hospital were retrospectively analyzed. Demographic and clinicopathological variables independently correlated to VTE were applied to develop the risk score in the development group while examined in the validation group. The regression coefficients of multivariable logistic regression test we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 29 publications
5
43
0
Order By: Relevance
“…Based on our analysis, the results showed that patients with adenocarcinoma have an approximately 3-fold higher risk of developing VTE than that of non-adenocarcinom apopulation. This result is consistent with the findings of previous studies (19,21,35). There is also clear evidence that patients with adenocarcinoma was associated with a markedly higher risk of VTE compared with other pathological types (8,35).…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Based on our analysis, the results showed that patients with adenocarcinoma have an approximately 3-fold higher risk of developing VTE than that of non-adenocarcinom apopulation. This result is consistent with the findings of previous studies (19,21,35). There is also clear evidence that patients with adenocarcinoma was associated with a markedly higher risk of VTE compared with other pathological types (8,35).…”
supporting
confidence: 94%
“…score system (19)(20)(21). However, few studies have been performed for the development of novel nomograms for the prediction of VTE in lung cancer patients, particularly given other factors influencing cancer-associated VTE such as genetic and therapeutic factors (31).Therefore, with a specific focus on both genetic and therapeutic factors, we developed and validated a simple yet highly discriminating, well-calibrated, and parsimonious nomogram prediction model for the occurrence of VTE in hospitalized lung cancer patients in this study, which can provide a theoretical basis for clinical decision-making on Decision curve analysis (DCA) for assessment of the clinical utility for thromboprophylaxis.…”
mentioning
confidence: 99%
“…Smoking [ 25 ] and recent hospitalisation [ 23 , 24 ] also raise the risk of VTE. It is believed that the Asian race has a lower risk than other races [ 26 ]. Factor V Leiden and prothrombin 20210A mutations are relatively common in Caucasians whereas they are very rare in Asians [ 27 , 28 ].…”
Section: Vte Risk Factors In Ambulatory Patients With Lung Cancermentioning
confidence: 99%
“…Cancer treatment is a strong risk factor for VTE, and commonly used chemotherapy drugs can increase the risk of this clinical condition [ 25 , 26 , 36 ]. For example, gemcitabine-based chemotherapy increases the risk of VTE, with a reported odds ratio of 3.37 (95% CI 1.09–10.39) [ 23 ].…”
Section: Vte Risk Factors In Ambulatory Patients With Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation